Rare malignant cases of unilateral bleeding nasal mass: case series - Krishna, Kondreddy Siri; Mohanty, Deeganta; Harini, Boddikuri (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
A complete assessment of nasal masses along with early diagnosis and management of the disease is very important to prevent complications. Epistaxis and nasal obstruction are the signs of suspicion of malignant tumors. Patient‘s presentation depends upon the site and extent of the mass. This article comprises of study done on Three patients who presented to the department of otorhinolaryngology (ENT) with nasal mass with symptoms of nasal obstruction and nasal bleeding. All patients were subjected to clinical examination, diagnostic nasal endoscopy, radiological evaluation, surgical intervention and histopathological assessment. Thorough assessment helps the surgeon to come to a diagnosis which includes even rare cases and helps to treat the disease and to prevent further progression of the disease and it’s complications.